The Birth of East-Belgian Identity and the Treaty of Versailles. A Critical Legal Analysis - Vanhullebusch, Matthias (Nationalities Papers, 2025)
„In the former districts of Eupen and Malmedy, present-day East-Belgians, in particular academic and socio-political elites, draw their collective identity, amongst others, from the historical injustices inflicted upon them ever since the adoption of the Treaty of Versailles. The transfer of sovereignty from Germany to Belgium was then the subject of a popular consultation organised by the transitional Belgian authorities in those territories. Favouring national over popular sovereignty, those authorities de facto undermined the freedom of choice and imposed their annexation to Belgium which the League of Nations, despite criticisms, consecutively endorsed. Much has been said about this petite farce belge yet not from a legal point of view. Thus, this article sheds a different light on the historical accounts of those events which are instrumentalised to construct the contemporary collective identity of the German-speaking Community of Belgium.“
Keywords: Identität; Nationalismus; Versailler Vertrag (1919)

„A trip organised for children is not a serious matter“? Summer treatment camps for the Belgian-German borderlands (1919–1939). - Venken, Machteld (Childhood, 2025)
„Although the children whose rural homelands transitioned from German to Belgian state sovereignty following the First World War were not the typical demographic targeted for preventive air treatments against tuberculosis, they were overrepresented in treatment camps in both Belgium and Germany. Nation-state representatives provided public and private (although partly state subsidized) treatment camps to restore the physical vitality, ethical integrity, and national allegiances of the minors. The parallel competitive offer took the form of a cross-border mixed economy of child welfare. Borderland residents either opportunistically supported the Belgian or German initiatives, or provided their own alternatives to protect their children from indoctrination.“
Keywords: Heilanstalt; Jugend; Kind; Nationalbewusstsein; Nationalismus; Nationenbildung; Verschickung

„Deutsche“, „Holländer“, und „Grafschafter“. Zur Konstruktion regionaler Identität in der Grafschaft Bentheim 1866–1918 - Zurek, Steven (Aschendorff Verlag, 2024)
Aus den Verlagsangaben: „In dem Buch wird die Konstruktion regionaler Identität(en) in der Grafschaft Bentheim im Zeitraum von 1866 bis 1918 untersucht. 1866 fiel die einst jahrhundertelang als Reichsgrafschaft eigenständige Region an das Königreich Preußen. Es wird aufgezeigt, welche als regionale Spezifika der Grafschaft Bentheim ausgewiesenen Aspekte in dieser Zeit zur Konstruktion regionsbezogener Identität(en) herangezogen sowie von der bentheimischen Bevölkerung wahrgenommen wurden und so Einfluss auf die Selbstzuordnung breiter Teile der Bevölkerung hatten. Es wird herausgearbeitet, dass es maßgeblich die als gemeinsam ausgewiesene Geschichte der einst eigenständigen Reichsgrafschaft Bentheim, die reformierte Konfession der Bevölkerungsmehrheit, die sprachliche Affinität zum Niederländischen, die Prägung durch die Grenzlage und die damit zusammenhängenden ökonomischen und privaten Verflechtungen mit den Niederlanden, das Fürstenhaus als gesellschaftlich weiterhin hochbedeutsames Symbol ursprünglicher Eigenstaatlichkeit sowie regionale Traditionen waren, die dafür herangezogen, als relevant ausgewiesen und angesehen wurden. Darüber hinaus wird in den Blick genommen, mit welchen Maßnahmen versucht wurde, diese regionale(n) Identität(en) mit einer (preußischen) Landes- und (deutschen) Nationalidentität im Sinne multipler Identität(en) zu harmonisieren.“
Inhaltsverzeichnis: https://digitale-objekte.hbz-nrw.de/storage2/2024/07/20/file_20/9575337.pdf
Keywords: Grafschaft Bentheim; Grenzgebiet; Hochschulschrift; Nationalbewusstsein; Nationalismus; Regionale Identität

Vom Europäischen Krieg zum Weltkrieg. Militär und Kriegserfahrung während 130 Jahren - Liemann, Bernhard; Beck, Philippe; Quadflieg, Peter M.; Rohrkamp, René (Code civil, beschleunigte Moderne und Dynamiken des Beharrens (1794–1919), 2017)
Keywords: Grenzgebiet; Militär; Nationalismus

Nationalization campaigns and teachers’ practices in Belgian–German and Polish–German border regions (1945–1956) - Venken, Machteld (Nationalities Papers, 2014)
Keywords: Belgien; Bildungswesen; Deutschland; Eupen-Malmedy; Lehrer; Nationalismus; Polen; Schule; Sprachpolitik

La frontière, miroir des conceptions de l’État à l’époque moderne - Moreau de Gerbehaye, Claude de (Revue belge de philologie et d'histoire, 2013)
Abstract: „La frontière signifie bien davantage qu’un simple tracé linéaire sur une carte géographique. Car ce tracé est une limite territoriale porteuse de pouvoirs politiques et de souveraineté. La frontière a connu des expressions différentes au fil des siècles : les tracés géométriques contemporains marquent les esprits à tel point (de la ligne bleue des Vosges, au rideau de bambou, au mur israélien en construction) que d’autres expressions deviennent impensables. Elles sont l’expression contemporaine de notions remontant à l’Antiquité (limes, mur d’Hadrien) et remises à l’honneur aux temps modernes (pré carré, frontières «naturelles » ) avec la résurgence de l’État. Une attention particulière est portée sur les modalités d’expression des séparations entre entités politiques : zones, condominium, enclaves territoriales, dépendances personnelles. Ensuite, le concept de frontière sera observé à la lumière de ceux d’État et de nation, ainsi que son positionnement (cause ou de conséquence) à l’égard de ces derniers, avec les dérives qui peuvent en découler.“
Keywords: Nationalismus; Staatsgrenze

Vom Bestreben, "auch an den äußersten Westmarken nach Kräften der vaterländischen Sache zu dienen". Die rheinpreußischen Grenzkreise Eupen und Malmedy 1815–1914 - Scharte, Sebastian (Transregionale Perspektiven. Kleinräumige Mobilität und Grenzwahrnehmung im 19. Jahrhundert, 2011)
Keywords: Nationalbewusstsein; Nationalismus; Ostbelgien; Staatsgrenze

Von Staatsgrenzen zu nationalen Grenzen - Nordman, Daniel (Die Grenze als Raum, Erfahrung und Konstruktion. Deutschland, Frankreich und Polen vom 17. bis zum 20. Jahrhundert, 2007)
Keywords: Nationalbewusstsein; Nationalismus; Nationenbildung; Staatsgrenze

Nationalisme en de grens - Dijk, Joop van; Oppel, Hans; Wilterdink, Willem (Grenzen komen en gaan, kommen und gehen, 1993)
Keywords: Nationalismus

Nationalismus und Grenze - Dijk, Joop van; Oppel, Hans; Wilterdink, Willem (Grenzen komen en gaan, kommen und gehen, 1993)
Keywords: Nationalismus